Modern approaches to the introduction of higher education degrees for the speciality 226 Pharmacy, industrial pharmacy - I. V. Bushuyeva; N. O. Tkachenko; O. A. Kremzer; V. M. Odyntsova; L. G. Cherkovska (The State Expert Center of the Ministry of Health of Ukraine, 2023)
The main direction of the development of the education system in Ukraine is the introduction of European standards, technologies, norms, and perspectives to ensure competitiveness in the market of European education services. The study aimed to highlight modern approaches to the standardization of higher education in the context of shaping professional competences of future pharmacists, to identify peculiarities and possibilities of applying a systemic approach to the development of a higher education standard for the specialty of 226 Pharmacy, Industrial Pharmacy of the second (master's) level. The research materials consisted of references containing information on the development, approval, and implementation of higher education standard. The following methods were used in the study: synthetic, analytical, information search, descriptive, and generalization. The pharmaceutical industry is socially significant, and the specialty of 226 Pharmacy, Industrial Pharmacy, as well as all the specialties in the field of study 22 Health, are regulated. Therefore, professionals in this field should possess integrated knowledge and skills, be able to solve complex tasks and problems in the field of pharmacy and healthcare, both in practice and during the learning process. This involves conducting research, implementing innovations, and is characterized by uncertain conditions and requirements. A modern approach also involves the use of highly efficient technologies in the national and international educational and scientific environments, which ensure the preparation of competitive, highly qualified pharmaceutical professionals with moral and spiritual values, social responsibility, and community orientation. They are capable of providing quality pharmaceutical care to people and possess «soft skills». Upon the development of the approved higher education standard for the specialty of 226 Pharmacy, Industrial Pharmacy by the Ministry of Education and Science of Ukraine, the educational and professional programs Pharmacy and Perfume and Cosmetic Technologies were revised, and a list of competences as well as program learning outcomes for future pharmaceutical professionals was specified. These were aligned with the demands of the labor market and a professional-oriented approach, based on the concept of competences for a modern pharmacist and the variable components of educational and professional training programs